A Cross-sectional to determine how Knowledgeable pregnant Women attending Antenatal Care at Lira Regional Referral Hospital are regarding the benefits and contraindications of Physical Activity during Pregnancy. - Felex Okori (Student's Journal of Health Research, 2022)
Background.  Physical activity during pregnancy provides many health benefits not only to pregnant mothers but also to the fetuses. Adequate knowledge among pregnant mothers is vital to enhance positive attitudes. This study assessed knowledge of pregnant women on PA in pregnancy among pregnant women attending ANC in Lira Regional Referral Hospital. Methods.  The cross-sectional study of 152 pregnant women attending antenatal clinic visits in Lira Regional referral Hospital, northern Uganda. Data were obtained on socio-demographic characteristics of mothers, knowledge, and attitude towards PA in pregnancy. Results.  Decreasing the risk of swelling of extremities (65%), back pain (73%), and high blood pressure (80%), and promoting a better ability to cope with labor and delivery (72%) were the most commonly known benefits of PA in pregnancy and vaginal bleeding (80%), chest pain (70%), difficulty in breathing (77%), abdominal pain (72%), premature labor (73%), muscle weakness and migraine headache (73%) were perceived contraindications of physical activity during pregnancy. 46% had adequate overall knowledge of PA during pregnancy. The knowledge of women was influenced by gestational age (p=0.007) and level of education (p=0.014).  Conclusion.  The majority of women demonstrated inadequate knowledge of physical activity during pregnancy. Mothers had a fair knowledge of the benefit, but the majority had minimal information about the contraindication and when to start and stop physical activity when they get pregnant. Recommendation Based on the findings, women in this study didn't have comprehensive knowledge about PA during pregnancy, health care providers should be empowered to counsel healthy and fit pregnant women with comprehensive, evidence-based prenatal exercise guidelines on the safety of involvement in PA during pregnancy.